Janus-Faced Paradigms - Gúti, Erika; T. Horváth, Attila (Afrika Tanulmányok / Hungarian Journal of African Studies, 2019)
The paper examines the parallel existence of the global paradigm ‘linguistic imperialism’ and the linguistic/cultural paradigm in the African language system, which in their own right can have positive or negative effects, too. The other question that the paper looks at is the role of the great African lingua francas (e.g., Swahili) in this system.